Memanfaatkan Transformasi Digital untuk Mempercepat Investasi Berkelanjutan Melalui Integrasi Lingkungan, Sosial, dan Tata Kelola (ESG) - Kusuma, Ajeng Pramesthy Hardiani; Jumantoro, Tegar Raffi Putra (Veteran Law Review, 2025)
In recent years, digital transformation has emerged as a pivotal catalyst for innovation and efficiency across various sectors, including sustainability. This study investigates the integration of digital technology with Environmental, Social, and Governance (ESG) principles to enhance the sustainable industrial sector in Indonesia. Despite the presence of supportive policies, challenges such as the effective implementation of digital technology and the preparedness of human resources remain significant barriers to achieving this objective. Employing a normative approach, this research analyzes the legal framework governing sustainable investment in Indonesia and assesses the potential of digital technology in accelerating ESG adoption within the industrial sector. Furthermore, it proposes strategic recommendations to cultivate an ecosystem that facilitates digital transformation, emphasizing regulatory measures that reinforce the synergy between technology, sustainability, and investment. The findings of this study are expected to provide valuable insights for policymakers, industry stakeholders, and investors in advancing sustainable investment through digital innovation in Indonesia.